2020
DOI: 10.1101/2020.04.02.022384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

One-step RNA extraction for RT-qPCR detection of 2019-nCoV

Abstract: The global outbreak of coronavirus disease 2019 has placed an unprecedented burden on healthcare systems as the virus spread from the initial 27 reported cases in the city of Wuhan, China to a global pandemic in under three months 1 . Resources essential to monitoring virus transmission have been challenged with a demand for expanded surveillance. The CDC 2019-nCoV Real-Time Diagnostic Panel uses a real-time reverse transcription quantitative polymerase chain reaction (RT-qPCR) consisting of two TaqMan probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…In one report, positive patient swab samples diluted 1:1 into Quick Extract DNA extraction solution (a buffer containing detergents and proteinase K), heat inactivated and directly added to the RT-PCR reaction mix were detected at the same amplification cycle as, or even slightly before, samples processed with the QIAmp Viral RNA Miniprep kit (Qiagen) (Ladha et al). Another group reported that swab samples added to Quick Extract DNA extraction solution were detected with equal sensitivity to column-purified RNA (Sentmanat et al 2020). Finally, another study reported that direct addition of swab samples treated 15 minutes with proteinase K yielded sensitivity comparable to the use of RNA isolated with the automated ELITe InGenius Sp200 system (ELITech Group) (Marzinotto et al).…”
Section: Rtmentioning
confidence: 99%
“…In one report, positive patient swab samples diluted 1:1 into Quick Extract DNA extraction solution (a buffer containing detergents and proteinase K), heat inactivated and directly added to the RT-PCR reaction mix were detected at the same amplification cycle as, or even slightly before, samples processed with the QIAmp Viral RNA Miniprep kit (Qiagen) (Ladha et al). Another group reported that swab samples added to Quick Extract DNA extraction solution were detected with equal sensitivity to column-purified RNA (Sentmanat et al 2020). Finally, another study reported that direct addition of swab samples treated 15 minutes with proteinase K yielded sensitivity comparable to the use of RNA isolated with the automated ELITe InGenius Sp200 system (ELITech Group) (Marzinotto et al).…”
Section: Rtmentioning
confidence: 99%
“…In addition, a rapidly accumulating list of publications and pre-prints describe protocols that allow bypassing some of the rate limiting steps in the diagnostic protocol [92,[119][120][121]. For example, RNA extraction can be substituted by simply heating the sample to 95˚C for 10 minutes [92,121].…”
Section: Fosh Approaches In Covid-19 Diagnosticsmentioning
confidence: 99%
“…Local manufacturing of health technologies depends on the presence of relevant capacity, infrastructure and regulatory frameworks but is promoted by organisations including the WHO, UNIDO, UNCTAD, UNAIDS, UNICEF and The Global Fund [127]. The implementation of low-cost diagnostic technologies in countries with very limited testing resources could be a game changer in the global control of the COVID-19 pandemic, particularly when combined with protocols for RNA extraction that do not depend on commercial kits ( [90][91][92]119,121], and Table 3), and the generation of reagents that can be distributed and stored at room temperature [128]. For this reason, development of rapid diagnostics for use at the community level was #1 in the WHO's eight immediate research actions agreed as part of their 2019 Novel Coronavirus Global Research and Innovation Forum [129].…”
Section: Fosh Approaches In Covid-19 Diagnosticsmentioning
confidence: 99%
“…Alternatively, RNA extractions could be performed on saliva for which clinically-relevant methods now exist, however, this would still add considerable costs and labour (Pandit et al 2013;Sullivan et al 2020) . Methods for one-step RNA extractions may provide a compromise between direct qRT-PCR and complete RNA extraction (Sentmanat et al 2020) .…”
Section: Discussionmentioning
confidence: 99%